A novel and effective strategy for the treatment of large hepatic hemangioma: combining preoperative embolization with laparoscopic-assisted and ultrasound-guided ablation - Xin Jin; Ziman Zhu; Wei Zhao; Liyuan Sun; Bin Hu; Hongbo Huan; Yuliang Tu; Dadong Wang; Kai Jiang (World Journal of Surgical Oncology)
Abstract Background Hepatic hemangioma is the most common benign liver tumor. This study aims to evaluate the feasibility, safety and efficacy of Trans-arterial embolization (TAE) combined with thermal ablation in the treatment of large hepatic hemangioma (> 5 cm). Methods From January 2018 to December 2021, 82 patients and 112 large HH with a maximum mean diameter of 8.24 ± 0.26 cm (range: 4.3–16.0 cm) and a cumulative diameter of 9.45 ± 0.45 cm (range:5.0–29.6 cm) were treated with laparoscopic-assisted and ultrasound (US)-guided percutaneous radiofrequency ablation (RFA) or microwave ablation (MWA) during a single general anesthesia episode following TAE. After surgery, therapeutic efficacy was assessed by contrast-enhanced imagings during follow-up. Median follow-up time was 14 months (range: 2–48 months). Results All patients have a mean operating time of 79.10 ± 2.59 min. The plain CT revealed that 112 treated lesions were totally covered (100%). Hemoglobinuria was detected in 28 patients (34.1%), and there were no cases of acute renal failure. Abdominal pain occurred in 40 patients (48.8%), while peritoneal effusion in six (7.3%). Acute cholecystitis developed in 11 patients (13.4%), constipation in five (6.1%), and nausea and vomiting in 14 (17.1%). According to the Clavien–Dindo classification, 54 patients (65.9%) had minor complications, while none had severe complications. The follow-up, no Hepatic hemangioma growth was observed. Conclusion Preoperative TAE combined with thermal ablation is a novel therapeutic strategy for large HH. This strategy is simple, less risky, and feasible.